A Thermodynamic Description of Turbulence as a Source of Stochastic Kinetic Energy for 3D Self‐Assembly. Issue 5 (18th July 2019) - Löthman, Per A.; Hageman, Tijmen A. G.; Elwenspoek, Miko C.; Krijnen, Gijs J. M.; Mastrangeli, Massimo; Manz, Andreas; Abelmann, Leon
Abstract: The extent to which one can use a thermodynamic description of turbulent flow as a source of stochastic kinetic energy for 3D self‐assembly of magnetically interacting macroscopic particles is investigated. It is confirmed that the speed of the objects in the flow field generated in this system obeys the Maxwell–Boltzmann distribution, and their random walk can be defined by a diffusion coefficient following from the Einstein relation. However, it is discovered that the analogy with Brownian dynamics breaks down when considering the directional components of the velocity. For the vectorial components, neither the equipartition theorem nor the Einstein relation is obeyed. Moreover, the kinetic energy estimated from the random walk of individual objects is one order of magnitude higher than the value estimated from Boltzmann statistics on the interaction between two spheres with embedded magnets. These results show that introducing stochastic kinetic energy into a self‐assembly process by means of turbulent flow can to a great extent be described by standard thermodynamic theory, but anisotropies and the specific nature of the interactions need to be taken into account. Abstract : Introducing stochastic kinetic energy into a self‐assembly process of macroscopic magnetic particles by means of turbulent flow can be described by standard thermodynamic theory. The speed of the particles obeys the Maxwell–Boltzmann distribution, and their random walk can be defined by a diffusion coefficient following from the Einstein relation. The directional components differ to some extent.